Characterization of biomaterial‐free cell sheets cultured from human oral mucosal epithelial cells. (19th November 2014) - Hyun, Dong Won; Kim, Yun Hee; Koh, Ah Young; Lee, Hyun Ju; Wee, Won Ryang; Jeon, Saewha; Kim, Mee Kum
Abstract: The purpose of this study was to report the characteristics of biomaterial‐free sheets cultured from human oral mucosal epithelial cells without fibrin support, in vitro and after transplantation to limbal‐deficient models. Human oral mucosal epithelial cells and limbal epithelial cells were cultured for 2 weeks, and the colony‐forming efficiency (CFE) rates were compared. Markers of stem cells (p63), cell proliferation (Ki‐67) and epithelial differentiation (cytokeratin; K1, K3, K4, K13) were observed in colonies and in biomaterial‐free sheets. Biomaterial‐free sheets which had been detached with 1% dispase or biomaterial‐free sheets generated by fibrin support were transplanted to 12 limbal‐deficient rabbit models. In vitro cell viability, in vivo stability and cytokeratin characteristics of biomaterial‐free sheets were compared with those of sheets formed by fibrin‐coated culture 1 week after transplantation. Mean CFE rate was significantly higher in human oral mucosal epithelial cells (44.8%) than in human limbal epithelial cells(17.7%). K3 and K4 were well expressed in both colonies and sheets. Biomaterial‐free sheets had two to six layers of stratified cells and showed an average of 79.8% viable cells in the sheets after detachment. Cytokeratin expressions of biomaterial‐free sheets were comparable to those of sheets cultured by fibrin support, in limbal‐deficient models. Both p63 and Ki‐67 were well expressed in colonies, isolated sheets and sheets transplanted to limbal‐deficient models. Our results suggest that biomaterial‐free sheets cultured from human oral mucosal epithelial cells without fibrin support can be an alternative option for cell therapy in use for the treatment of limbal‐deficient diseases. Copyright © 2014 John Wiley & Sons, Ltd.